COVID-19 in older people: a rapid clinical review. (6th May 2020) - Lithander, Fiona E; Neumann, Sandra; Tenison, Emma; Lloyd, Katherine; Welsh, Tomas J; Rodrigues, Jonathan C L; Higgins, Julian P T; Scourfield, Lily; Christensen, Hannah; Haunton, Victoria J; Henderson, Emily J
Abstract: Introduction: the COVID-19 pandemic poses a high risk to older people. The aim of this article is to provide a rapid overview of the COVID-19 literature, with a specific focus on older adults. We frame our findings within an overview of the disease and have also evaluated the inclusion of older people within forthcoming clinical trials. Methods: we searched PubMed and bioRxiv/medRxiv to identify English language papers describing the testing, treatment and prognosis of COVID-19. PubMed and bioRxiv/medRxiv searches took place on 20 and 24 March 2020, respectively. Results: screening of over 1, 100 peer-reviewed and pre-print papers yielded n = 22 on COVID-19 testing, n = 15 on treatment and n = 13 on prognosis. Viral polymerase chain reaction (PCR) and serology are the mainstays of testing, but a positive diagnosis may be increasingly supported by radiological findings. The current evidence for the effectiveness of antiviral, corticosteroid and immunotherapies is inconclusive, although trial data are largely based on younger people. In addition to age, male gender and comorbidities, specific laboratory and radiology findings are important prognostic factors. Evidence suggests that social distancing policies could have important negative consequences, particularly if in place for an extended period. Conclusion: given the established association between increasing age and poor prognosis in COVID-19, we anticipate that this rapid review of the current and emergent evidence might form a basis on which future work can be established. Exclusion of older people, particularly those with comorbidities, from clinical trials is well recognised and is potentially being perpetuated in the field of current COVID-19 research.